The outbreak of Ebola virus disease in 2022: A spotlight on a re-emerging global health menace - Al-Tammemi, Ala'a B.; Sallam, Malik; Rebhi, Asem; Soliman, Laarni; Al Sarayrih, Lina; Tarhini, Zeinab; Abutaima, Rana; Aljaberi, Musheer A.; Barakat, Muna (Narra J, 2022)
Ebola virus disease (EVD) is a rare but highly contagious and lethal disease that occurs predominantly in African countries, with a case-fatality rate of 30–90%. The causative viral pathogens of EVD are within the genus Ebolavirus in the family Filoviridae. The primary route of human-to-human transmission is through direct contact with blood, bodily fluids and secretions from infected individuals. Direct contact with virally contaminated objects and sexual transmission have also been reported. Management of EVD is aggressive supportive care with possibly new therapeutic options. On 20 September 2022, an EVD outbreak was declared in Uganda, caused by Sudan ebolavirus. As of 7 November 2022, a total of 136 confirmed cases, 53 confirmed deaths have been reported, including 18 cases with seven deaths among healthcare workers. In the Democratic Republic of Congo (DRC), an EVD outbreak was also declared on 22 August 2022 (which ended on 27 September 2022); with only one case, a middle-aged woman. At the time when most countries in the world have been occupied with the coronavirus disease 2019 (COVID-19) pandemic and the recent human monkeypox outbreak, these two outbreaks of EVD have the potential to significantly add to the burden on global health. Authorities need to augment their multi-faceted response, including stringent contact tracing and border control, to avoid the catastrophe of the 2014–2016 EVD epidemic.